Analisis Pengaruh Penjualan Personal dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk pada UD Kembar Fashion di Kecamatan Tigapanah, Kabupaten Karo - Jhona Boy Erwinta Sembiring; Sri Rezeki (Lembaga Pengembangan Kinerja Dosen, 2025)
The decline in sales experienced by UD Kembar Fashion in Tigapanah District over the past five years is the main focus of this study. This condition is thought to be closely related to the company's suboptimal implementation of personal selling strategies and the low quality of service provided to potential customers. Personal selling as a marketing strategy plays a crucial role in building direct communication with customers, so weaknesses in its implementation can lead to decreased purchasing interest. Likewise, suboptimal service quality can reduce customer satisfaction and trust in the company, thus affecting purchasing decisions. The purpose of this study is to determine and analyze the extent to which personal selling and service quality, both partially and simultaneously, influence product purchasing decisions at UD Kembar Fashion. This study uses an associative quantitative method with an explanatory approach. The study population is potential customers shopping at UD Kembar Fashion, and 104 respondents were selected using an accidental sampling technique. Data were collected through questionnaires, then analyzed using multiple linear regression tests with the help of the SPSS version 25 program. The results show that partially, personal selling has a positive and significant effect on consumer purchasing decisions. The same holds true for the service quality variable, which proved to have a positive and significant influence. Simultaneously, both variables significantly influenced purchasing decisions. This finding indicates that enhancing a more intensive personal selling strategy and improving service quality could be a strategic solution to encourage increased consumer purchasing decisions at UD Kembar Fashion, thereby reversing the declining sales trend.